Orion Wire and Cable Inc A production systems study - Eiaw, Sherilyn Uy; Lam, Anna Grace A.; Salva, Claire L. (Diliman, Quezon City College of Engineering, 1999)
Orion Wires and Cable, Inc. manufactures a limited array of electric cords and wires for hardware and housing development projects. It is situated in 88 Kaingin Road, Balintawak, Quezon City. The company is applying for ISO 9002 certification. The groups aims to study and improve the existing production system of the company through the application of production and operations management techniques. By analyzing the present organization and system of the company enabled the group to diagnose the various problems encountered by the company's internal system. Inconsistent production scheduling and insufficient manpower and insufficient supervision are among the problems faced by the company. The group has also noticed the effects of insufficient materials, poor forecasting techniques, low demand, and inefficient work have on the production system. Through careful analysis of the company's issues, the group has been able to come up with several solutions to its problems. Among them are the applications of Economic Order Quantity, quantitative forecasting, motivation and incentives for the workers, improvement of job designs and possibility of hiring additional personnel.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Orion Wire and Cable Incorporated; Wire industry; Production engineering